Impact of Foreign Direct Investment on Economic Growth in Nigeria (1980 - 2018) - Adekoya, Oluwatoyosi Deborah (NIU Journal of Humanities, 2024)
Foreign Direct Investment (FDI) serves as a means through which developing economies earn overseas earnings through aid, business startups, and investments from developed nations. This study analyses the determinants of the inflows of FDI into Nigeria from 1991 – 2018 and its effect on the growth of the country. Data was obtained from different official sites such as the World Development Indicators (WDI), the National Bureau of Statistics (NBS), the Central Bank of Nigeria Bulletin (CBN), and the International Monetary Fund (IMF). Multivariate co-integration analysis (VAR) was employed to ascertain the relationship between the FDI and economic growth. After the first differencing, the variables became stationary at 0.05%. Johansen and Granger causality tests were conducted to check for causality between foreign direct investment and economic output. The outcome showed that openness to trade, exchange rate, and infrastructural facilities contributed to output. The result of the study indicated that FDI is a significant measure of growth. Employing the multivariate times series data, it was concluded that the determinants of foreign direct investment include infrastructural facilities, openness to trade, and exchange rate which are positively related and statistically significant to economic growth. This study recommends that the government improve infrastructural facilities such as stable electricity supply, good roads, and a conducive environment to assure foreign expatriates about their safety and investment. This will boost investment inflow into society and reduce local investors’ emigration. Keywords : Exchange rate, Foreign Direct Investment, Gross Domestic Product, Vector Autoregressive Methods